Effect of rain on absorption after transdermal application of flunixin in calves. Issue 1 (13th December 2019) - Altenbrunner‐Martinek, Birgit; Witek, Martin; Koppatz, Karl; Freissmuth, Michael; Kraft, Alinta; Sutter, Charlene; Torres, Siddartha; Gelfert, Christian; Wittek, Thomas
Abstract: Flunixin is a nonsteroidal anti‐inflammatory drug (NSAID) that has anti‐inflammatory, anti‐pyretic, and analgesic effects. Recently, a novel transdermal formulation was developed (Finadyne ® Transdermal, MSD Animal Health) and is now the first NSAID registered to be administered as a pour‐on product in cattle. According to the manufacturer's instructions, the pour‐on product should be applied only to dry skin and exposure to rain should be avoided for at least 6 hr after application. The objective of the study was to evaluate the effect of simulated exposure to light or heavy rain on flunixin absorption and bioavailability within the first 4 hr after administration. Therefore, an isocratic HPLC method was developed to quantify flunixin concentrations in bovine serum by UV detection. Light rain decreased flunixin absorption only when rain started immediately after flunixin administration, while light rain starting more than 30 min after administration of flunixin had no effect on absorption. Absorption and bioavailability of flunixin was impacted under simulated heavy rain conditions, when exposure to rain occurred within one hour after the application of the pour‐on formulation, but not later.